Effect of Addition of Soursop Leaf Extract to Ganyong (Canna edulis Ker.) Starch Edible Film and its application in Red Grape Storage Time - Erni Widyastuti; Endaruji Sedyadi; Susy Yunita Prabawati (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2016)
This study aimed to determine the effect of addition of Soursop leaf extract to edible film and its effect on the storage time of red grapes. This research had three main steps, soursop leaf extraction, edible film making, and application on red grapes storage time. Soursop leaves extract variation used in this research are 0.5; 1; and 1.5% (w/w total) and the best result was used to coat the red grapes. The results showed that the optimum composition was obtained on the edible film with the addition of 0.5% (w/w total) soursop leaf extract. The composition increased film thickness from 0.03 to 0.08 mm, decreased film’s tensile strength from 11.89 to 8.42 MPa, decreased elongation from 12.71 to 11.03%, decreased the Young Modulus from 0.935 to 0.764 MPa, and decreased the vapor transmission rate from 7.45 to 6.55 g/m2.hour. The 50% shrinkage of weight and 50% texture damage are used as parameters to measure the Red grapes storage time. Based on weight shrinkage, red grapes storage time change from 24 days to 29 days by using an edible film coating without addition of extract, an extend to 32 days while using an edible film coating with addition of soursop leaf extract. Based on texture damage, red grapes storage time increased from 13 to 41 days if using an edible film coating without addition of extract, and increased to 40 days using an edible film coating with the addition of soursop leaf extract.